Uncovering the Relationship of Supply Chain Management and Firm Performance: Evidence from Textile Sector of Pakistan - Hussain, Zahid; Jusoh, Ahmad Bin; Sarfraz, Muhammad; Wahla, Khalil Ur Rehman (Information Management and Business Review, 2018)
The purpose of this research paper was to find the impact of the supply chain on firm performance in Textile firm of Pakistan. Data was collected through questioners in the month of March 2018, Approximately 30 questioners were distributed among the managers of the ten textile organizations in Faisalabad which are expected to have the best knowledge about the supply chain operations and its impact on the performance of the organization, all of them responded positively. It is found that dimensions associated with SCM methods as well as explain the connection amongst SCM methods, aggressive benefit, as well as firm performance. The actual study focuses on the causal associations in between SCM exercise, aggressive benefit as well as firm performance as well as ignores the actual feasible recursive associations.